A strain-rate cohesive fracture model of rocks based on Lennard-Jones potential. (January 2022) - Lin, Qindong; Li, Shihai; Gan, Yundan; Feng, Chun
Highlights: The essence of strain rate effect is the change in intermolecular microscopic parameters at high strain rate. Two key parameters are proposed to quantify the effect of high strain rate on the mechanical parameters of molecules. The changes in microscopic increasing factors k ε and k r have different effects on the force–displacement curve. The correspondence between microscopic increasing factors and macroscopic mechanical parameters is established. Abstract: To characterize the dynamic mechanical response of rocks during the initiation and propagation of cracks at a high strain rate, a strain-rate cohesive fracture model is established based on the Lennard-Jones potential and multi-scale model of rocks. The newly proposed model explains the micro-mechanism of strain rate effect from the molecular scale and establishes the potential energy function and force function. First, it is proposed that the strain rate effect arises due to the change of microscopic properties of molecules at a high strain rate. Thereafter, the potential energy function and force function of the strain-rate cohesive fracture model corresponding to the dynamic tensile and shear processes are established. Finally, the accuracy of the strain-rate cohesive fracture model is verified through numerical simulations. The results indicate that the strain-rate cohesive fracture model can accurately simulate the dynamic tensile failure and shear failure of rocks at different strain rates. The dynamic tensile strength, dynamic compressive strength, and dynamic tensile fracture energy obtained by numerical simulations and laboratory tests are similar.